2004
DOI: 10.1128/iai.72.12.7326-7329.2004
|View full text |Cite
|
Sign up to set email alerts
|

Two tonB Systems Function in Iron Transport in Vibrio anguillarum , but Only One Is Essential for Virulence

Abstract: We have identified two functional tonB systems in the marine fish pathogen Vibrio anguillarum, tonB1 and tonB2. Each of the tonB genes is transcribed in an operon with the cognate exbB and exbD genes in response to iron limitation. Only tonB2 is essential for transport of ferric anguibactin and virulence.Outer membrane receptors for ferric siderophores require energy to internalize the complexed iron. This energy is transduced from the proton motive force in the inner membrane to the outer membrane receptor by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(76 citation statements)
references
References 21 publications
2
74
0
Order By: Relevance
“…Besides, the TonB1 gene cluster was shown to specifically contribute to haemin and haemoglobin utilization in this fish pathogen . In the same way, two different iron-regulated TonB mechanisms were identified in L. anguillarum (Stork et al, 2004). The analysis of these systems revealed that TonB2 protein but not TonB1 is involved in the transport of the siderophores anguibactin and enterobactin and that TonB2 protein is essential for virulence of L. anguillarum, since the LD 50 value for the tonB2 mutant strain was more than 100-fold higher than that of the parental strain (Stork et al, 2004).…”
Section: Iron Acquisitionmentioning
confidence: 85%
“…Besides, the TonB1 gene cluster was shown to specifically contribute to haemin and haemoglobin utilization in this fish pathogen . In the same way, two different iron-regulated TonB mechanisms were identified in L. anguillarum (Stork et al, 2004). The analysis of these systems revealed that TonB2 protein but not TonB1 is involved in the transport of the siderophores anguibactin and enterobactin and that TonB2 protein is essential for virulence of L. anguillarum, since the LD 50 value for the tonB2 mutant strain was more than 100-fold higher than that of the parental strain (Stork et al, 2004).…”
Section: Iron Acquisitionmentioning
confidence: 85%
“…Other candidate genes and systems are, for example, iron acquisition systems linked to virulence mechanisms in several vibrios (Stork et al 2004). Iron acquisition in A. salmonicida is proposed to constitute a temperature-sensitive virulence factor, as siderophore production is only detected at ≤10°C.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Intriguingly, in contrast to the majority of pathogenic bacteria, A. salmonicida has not been shown to induce any extracellular protease activity or cytotoxicity in cell models although numerous experiments have been performed (Hjelmeland et al 1988, present study data not presented). Other candidate genes and systems are, for example, iron acquisition systems linked to virulence mechanisms in several vibrios (Stork et al 2004). Iron acquisition in A. salmonicida is proposed to constitute a temperature-sensitive virulence factor, as siderophore production is only detected at ≤10°C.…”
Section: Aliivibrio Salmonicida (Formerly Vibrio Salmonicidamentioning
confidence: 99%
“…It has a plug domain that blocks the open channel and extracellular loops that are needed for the initial binding to the siderophore (187). FatA then facilitates the transport over the outer membrane via an energy-dependent mechanism that requires the TonB system (16,188). The genes of the TonB system are encoded on the chromosome (16,188).…”
Section: Transportmentioning
confidence: 99%